Борис Шрамко — дослідник широкого хронологічного діапазону (до 100-річчя з дня народження) - Скирда, В.В. (Археологія, 2023)
Статтю присвячено науковій діяльності Бориса Андрійовича Шрамка (1921—2012), відомого в середовищі археологічного співтовариства дослідника ранньої залізної доби і насамперед Більського городища. Однак учений доклав чимало зусиль також до вивчення
пам’яток інших періодів — починаючи з кам’яного
віку й закінчуючи добою українського козацтва. Borys Andriiovych Shramko (1921 — 2012) is known as a researcher of the Early Iron Age, and first of all of the largest
settlement in Europe of that time — the Bilsk hillfort. However, in reality, the scholar also carried out the study of monuments
from other periods. Chronologically, the earliest in his research were the monuments of the Stone Age. B. A. Shramko discovered
and examined about 20 sites of this period (two Palaeolithic, one Mesolithic and 14 Neolithic) in the course of archaeological
exploration.
In the research legacy of the Kharkiv researcher, the Eneolithic era is represented by excavations of burial mounds of
the Yamna culture near Parkhomivka and Lyptsi villages. To this period is dedicated Shramko’s article about the emergence
of arable farming in the south of Eastern Europe. The researcher also discovered a significant number (143) of Bronze Age
settlements and carried out excavations at some of them (the villages of Pisky Radkivski, Liubivka, etc.). Excavations were also
made at burial mounds (Krasna Mohyla, Bezimenna Mohyla, etc.) and flat burials (Velyka Danylivka) of that time.
B. A. Shramko also paid attention to the sites of the Late Roman times. The scholar discovered about 50 settlements (some
of them were reseached) and excavated a cremation burial ground of the Cherniakhiv culture near Pavlukivka village. The inlet
burial of the Kyiv culture, investigated on a hill near the village of Duvanky, belongs to the same period. The researcher paid
considerable attention to the study of medieval sites among which the Donetsk hillfort held a special place. The monuments of
the Ukrainian Cossacks era (the 18th century fortresses remains on the Berek River banks) also came into the field of vision of
B. A. Shramko.